Death by jack-o-lantern - Morgan, Alexis (Morgan, Alexis. Abby McCree mystery., 2019)
The small town of Snowberry Creek, Washington, is gearing up for the Halloween Festival, and naturally Abby is on the planning committee. As part of her duties, she's picking up a pumpkin order from ornery farmer Ronald Minter. But what she finds instead is the farmer in the middle of his corn maze with a knife in his back. The police suspect a homeless veteran named Kevin Montgomery, who was seen arguing with Minter when the farmer accused him of trespassing and stealing pumpkins. Abby's tenant Tripp Blackston, a veteran himself who<U+2019>s been helping Kevin, is sure he<U+2019>s innocent. Together, Abby and Tripp follow the twists and turns of the case to corner the corn maze killer<U+2014>before someone else meets a dead end <U+2026>